RIBA DAN TRANSAKSI KEUANGAN MODERN DALAM PRESPEKTIF ISLAM - Dinda Luthfiaturrahmah Alhaq; Muhamad Zen (BORJUIS: JURNAL OF ECONOMY, 2025)
This study analyzes the relationship between Riba and modern financial transaction practices from an Islamic perspective. Riba, which is prohibited in Islamic teachings, has significant implications for social justice and economic welfare. By identifying various forms of Riba, this article provides in-depth insights into its impact on individuals and society. On the other hand, modern financial transactions, which often involve interest, present new challenges in the application of Sharia principles. Through comparative analysis, this research highlights the fundamental differences between traditional and modern financial mechanisms, as well as the resulting socio-economic consequences. This study also offers Sharia-compliant alternatives, such as profit-sharing financing, which can be implemented to create a more sustainable and ethical financial system. By referencing relevant case studies, this research aims to enhance understanding of the application of Islamic values in contemporary financial practices. In conclusion, this article recommends the necessity of collaboration among stakeholders to formulate policies that support financial transactions aligned with Sharia principles, in order to achieve inclusive and equitable economic welfare.